Mitigating food insecurity through mallard duck egg production: The case of a rural community in the Philippines - Lagasca, Armando Dela Cruz; Duria, Jerski Jarzen Cajuigan; Baltazar, Eugenia Gaspar; Saturno, Janet Orden (Asian Journal of Agriculture and Rural Development, 2023)
Poverty, food insecurity, and lack of employment opportunities are fundamental issues experienced in the rural Philippines. They were worsened by the COVID-19 pandemic, which adversely impacted vulnerable sectors. This study examined the potential and viability of mallard duck egg production in a rural community in the Philippines. Twelve (12) rural women in Licab, Nueva Ecija, received 482 heads of ready-to-lay mallard ducks (Itik Pinas breed) as part of the Department of Agriculture Regional Field Office III’s livelihood initiatives. Data were gathered using a participatory research design through a household profile survey, focus group discussion, and descriptive statistics. The study findings showed that the respondents live below the poverty line and have an average monthly income of ₱2,083.33. The study revealed that during the 18 months of egg production, the recipients were able to harvest a total of 144,534 eggs. This provided the respondents with a gross income of ₱929,838.75 and a net gain of ₱341,156.89, corresponding to an average monthly net income of 1,579.43 per respondent. This allowed each respondent to improve their household income by up to 64.12%. Peak egg output was 76% or 60.33% on average. This study also showed the resiliency of rural women, who utilized locally accessible resources to reduce production costs.